COMPANY PERFORMANCE MODEL BASED ON STRATEGIC ALLIANCES, STRATEGIC INNOVATION AND SOCIAL MEDIA FOR CONTEMPORARY BEVERAGE PRODUCTS - Sudarman, Daman; Hananto, Djoko; Dadang, Dadang; Hasan, Diana (Universitas Muhammadiyah Tangerang, 2024)
The aim of this research is to see how the performance of contemporary beverage companies is influenced by Strategic Alliances, Strategic Innovation mediated by Social Media. This research method was designed with a quantitative approach, namely an approach that emphasizes aspects of social behavior that can be calculated and patterned. This research is based on the prositivism paradigm, namely research based on objectivity and intelligence to produce knowledge. The research results show that Strategic Alliances do not have a positive effect on Company Performance directly but must be through Social Media, while Strategic Innovation has a direct effect and through Social Media on Marketing Performance.